PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KREDIT BERMASALAH PADA PT. BANK PERKREDITAN RAKYAT (BPR) PEMBANGUNAN KERINCI - Putra, Dori HP (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the influence of three variables, namely internal factors (X1) and external factors (X2) on non-performing loans (Y) at PT. People's Credit Bank (BPR) Kerinci Development. The type of research used was quantitative research by distributing questionnaires to 63 samples in the status of non-performing credit debtors. Sampling using the Slovin formula. The method used is multiple linear regression with the help of SPSS 22. The results of the t-test of the internal factor variable show that the tcount < ttable is 0.184 < 2.000 and the resulting signification value is 0.855 > 0.05, it can be concluded that the Internal Factor has no effect on non-performing loans while the external factor variable shows that the tcalculate > ttable i.e. –2.614 > 2.000, it can be concluded that external factors negatively affect non-performing loans and for the results of the F test internal and external factor variables show a ftable > calculation of 4.897 > 3.15 and the resulting significance value of 0.011 < 0.05 then it is concluded that Internal factors and External Factors simultaneously affect non-performing loans